The Role of Foreign Harem and Queen In The Fall of The Ottoman Empire: A Siyasah Shar'iyyah Perspective - Rahmi, Rahmi; Ilhamni, Ilhamni; Meirison, Meirison; Humairoh, Roza (Universitas Cokroaminoto Yogyakarta, 2025)
The article from this research aims to explain the role of women and foreign women in the Ottoman government, which had positive and negative impacts on the Empire. At first, the role of women was not very prominent in government. However, women behind the scenes produced strong leaders who could increase the age of this Empire and experience a period of glory starting with the reign of Usman I. In Sultan Suleiman the Magnificent, the role of foreign women and enslaved people became more prominent. Repeated attempts by women in power at the Ottoman court to take different roles profoundly affected the state's internal structure in the long term, especially in foreign diplomacy. The mothers and wives of the sultans could build entities within the state, and they had supporters from ministries and the army. It is worth noting that